1994
DOI: 10.1530/eje.0.1310489
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine alterations in the somatotropic and lactotropic axes in uremic men

Abstract: To investigate the pathophysiology of altered growth hormone (GH) and prolactin secretion in endstage renal disease, we sampled blood at 10-min intervals for 24 h and applied deconvolution analysis to calculate hormone half-lives and pulsatile secretion rates. Two-site immunoradiometric assays were employed to quantitate presumptively intact GH and prolactin in nine middle-aged men with chronic renal failure and 14 gender-, age-, body weight- and community-matched controls. We observed that the half-lives of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 0 publications
3
18
1
Order By: Relevance
“…Decreased clearance and increased production are responsible for the elevation of prolactin in CKD (26). Consistent with other studies, we found higher prolactin concentrations in patients with CKD (17).…”
Section: Discussionsupporting
confidence: 92%
“…Decreased clearance and increased production are responsible for the elevation of prolactin in CKD (26). Consistent with other studies, we found higher prolactin concentrations in patients with CKD (17).…”
Section: Discussionsupporting
confidence: 92%
“…Hyperprolactinemia was reported in patients with renal insufficiency [31]. We have not noticed any significant differences between the serum PRL level of stage III patients with (III/B) and without (III/A) renal impairment.…”
Section: Discussioncontrasting
confidence: 48%
“…GH synthesis may be reduced, normal, or even increased in CKD [35]. GH secretion is normal or low in late pre-pubertal and pubertal children with CRF [36]; whereas GH secretion rates are increased with increased GH burst frequency in pre-pubertal children and in adults with end-stage renal disease (ESRD) [36][37][38]. The release of GH in response to GHRH is increased in adults [39], whereas, in children, the mid-to-late adolescent increase in GH production fails to occur in CKD [36].…”
Section: Gh and Igf-i Circulating Levels In Ckdmentioning
confidence: 99%